Establishment of PIN1 knockout porcine fetal fibroblast cell lines via CRISPR/Cas9 mediated gene-targeting - WANG Wanyi; YUAN Yilin; LI Lin; WANG Ying; DAI Yifan; YANG Haiyuan (陆军军医大学学报, 2022)
Objective To knock out PIN1 gene of porcine fetal fibroblasts (PFFs) by clustered regular interval short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system in order to establish PIN1 knockout porcine fetal fibroblast cell lines. Methods Firstly, the homology of the PIN1 gene between humans and pigs was analyzed. Secondly, 2 sgRNAs targeting the second exon region of the porcine PIN1 gene were designed using online tools (http://crispor.tefor.net/) and then cloned into the pX330 (addgene #42230) skeleton plasmid. Finally, the PIN1 targeting plasmid and Neomycin resistant plasmid were co-transfected into PFFs. G418 screening was used to obtain resistant single-cell colonies. Sanger sequencing, qRT-PCR, and Western blotting were adopted to determine the PIN1 genotypes and expression levels, respectively. Results The bioinformatics analysis showed that the amino acid sequence consistency and similarity of human and pig PIN1 proteins were 98%, and the root-mean-square deviation (RMSD) value of their 3-dimensional structures was 0.014. Fifteen homozygous monoclonal cell lines with PIN1 gene knockout were obtained, and the PIN1 protein was disrupted entirely in those PIN1 knockout colonies at translational level. Conclusion The PIN1 gene is efficiently knocked out in PFFs by a double sgRNAs-guided CRISPR/Cas9 system, and the porcine fetal fibroblast cell lines with PIN1 gene knocked out are successfully established.